Antitrust law and economics - Kirkwood, John B. (Emerald, 2004)
This volume contains ten papers, by many prominent authors, examining antitrust issues of current interest. The first paper summarizes the other papers and presents original research on the meaning of consumer welfare and the sources of buyer power. The next five articles evaluate older antitrust cases to determine whether the decisions reached, the relief ordered, or both, enhanced consumer welfare. The seventh paper describes a new measure of efficiency that gives greater weight to consumer harm and applies it to a recent merger. The next paper explains a new way in which vertical foreclosure can enhance the market power of an upstream supplier. The ninth article refines an innovative technique for identifying substitutes among a set of differentiated products. The tenth paper confronts a contentious policy issue - the treatment of patent settlements in which the patent holder pays the challenger to exit the market - and concludes that they should be per se illegal.
Keywords: Antitrust law -- Economic aspects -- United States.; elektronické knihy; electronic books